2021
DOI: 10.1039/d0ta11689k
|View full text |Cite
|
Sign up to set email alerts
|

Sodium difluorophosphate: facile synthesis, structure, and electrochemical behavior as an additive for sodium-ion batteries

Abstract: NaPO2F2 prepared via a facile two-step reaction was characterized by structural analysis and used as an additive for sodium-ion batteries. The addition of NaPO2F2 formed a highly Na+-conductive SEI layer, which enhanced electrode performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 76 publications
1
11
0
Order By: Relevance
“…23 To overcome the above drawbacks, previous studies showed that uoroethylene carbonate (FEC) as an electrolyte additive enhances the cycling performance of NIBs. 26 Since such an electrolyte additive as FEC was considered to be crucial for Naion battery performance, much attention has been attracted on the development of new electrolyte components and additives for Na-ion batteries, e.g., sodium-diuoro(oxalato)borate as an electrolyte salt 27 and an additive, 28 a ternary additive of FEC, prop-1-ene-1,3-sultone, and 1,3,2-dioxathiolane-2,2-dioxide, 29 a quaternary additive, 28 sodium diuorophosphate, 30 and so on. Despite the recent advances of electrolyte additives, the systematic understanding of additive functionality is still underway.…”
Section: Introductionmentioning
confidence: 99%
“…23 To overcome the above drawbacks, previous studies showed that uoroethylene carbonate (FEC) as an electrolyte additive enhances the cycling performance of NIBs. 26 Since such an electrolyte additive as FEC was considered to be crucial for Naion battery performance, much attention has been attracted on the development of new electrolyte components and additives for Na-ion batteries, e.g., sodium-diuoro(oxalato)borate as an electrolyte salt 27 and an additive, 28 a ternary additive of FEC, prop-1-ene-1,3-sultone, and 1,3,2-dioxathiolane-2,2-dioxide, 29 a quaternary additive, 28 sodium diuorophosphate, 30 and so on. Despite the recent advances of electrolyte additives, the systematic understanding of additive functionality is still underway.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the C=C peak of the benzene ring in the initial electrode is observed clearly at 1504 cm −1 , but with the insertion of K + , this peak almost disappears, which could be the interaction of K + and the sp 2 carbon of the aromatic rings in the P‐COF@SWCNT. At the same time, the new peak at 833 cm −1 are assigned to PF 6 − , which is attributed to the solvated structure of potassium intercalated with the P‐COF framework [41] . The intensity of the C−O⋅⋅⋅K and PF 6 − peaks increased while discharging to 0.01 V. When the electrode is charged to 3 V, the intensity of the C−O⋅⋅⋅K and PF 6 − peaks reduced, suggesting that K + is extracted from the active sites, demonstrating that K + can be accommodated reversibly in P‐COF@SWCNT.…”
Section: Resultsmentioning
confidence: 90%
“…At the same time, the new peak at 833 cm À 1 are assigned to PF 6 À , which is attributed to the solvated structure of potassium intercalated with the P-COF framework. [41] The intensity of the CÀ O•••K and PF 6…”
Section: Methodsmentioning
confidence: 99%
“…31 To form a stable and protective interfacial layer, many film-forming additives were developed in sodium-ion batteries, including FEC, 141 VC, 142 succinic anhydride (SA), 143 and sodium difluorophosphates (NaDFP). 144 However, the majority of studies focused on the modification of carbonate-based electrolytes. There are only a few reports on additives in ether-based electrolyte.…”
Section: Characteristics Of Ether-based Electrolytesmentioning
confidence: 99%